Assessing the performance of IRI-2020 using GPS-TEC measurements in Türkiye under low solar activity conditions - Kayacik, Orhan; Dogan, Ali Hasan; Erdogan, Bahattin (TAYLOR & FRANCIS LTD, 2026)
Ionosphere is one of the major error sources for GPS since it is dispersive. TEC, which is an indicator of the state of ionosphere, can be determined by GPS. The global ionosphere models also provide TEC. IRI-2020 is one of the widely used empirical models to obtain ionospheric parameters. In this study, 92 GPS stations were analysed using GPS-TEC analysis software for three years (2019-2021). According to the results, the highest TEC values were obtained in 2021. Moreover, the largest RMSE values were generally obtained at the boundaries of the study area and the RMSE values in 2021 are larger than in other years.
Keywords: Total electron content; GPS; IRI-2020; ionosphere; Accuracy; EMPIRICAL-MODEL; ACTIVITY PERIOD; IRI; Engineering; Geology; Remote Sensing